The relationship between workplace violence, emotional exhaustion, job satisfaction and turnover intention among nurses during the COVID-19 pandemic - Gedik, Özlem; Ülke Şimdi, Refika; Kıbrıs, Şerife; (Sivuk), Derya Kara (SAGE Publications, 2023)
Objectives: Workplace violence is a major issue in society, business and healthcare settings. It adversely affects both employee safety and their ability to provide healthcare services. Aim: This study examined the association between workplace violence, emotional exhaustion, job satisfaction and turnover intention among nurses during the COVID-19 pandemic. Methods: We collected data from 513 nurses. We conducted ‘Process Macro’ analysis. Firstly, we included three mediators in the model: job satisfaction, workplace violence and emotional exhaustion. Secondly, we used work hours and anxiety as moderators of the relationship between workplace violence and turnover intention. Results: The findings revealed statistical significance that job satisfaction and workplace violence mediated the relationship between emotional exhaustion and nurse turnover intentions. Work hours and anxiety also moderated the relationship between workplace violence and nurses’ turnover intention. Conclusion: Respondents indicated that they were most affected by verbal violence during this time. Workplace violence is a negative factor that affects nurses’ work, affecting them physically and psychologically. This occupational risk should be considered when evaluating nurses exposed to violence, as it affects job satisfaction and turnover intentions. The main theoretical contribution of this research is the identification of the association between workplace violence, emotional exhaustion, job satisfaction and turnover intention among nurses during the COVID-19 pandemic. It is clear that the research findings will be useful for healthcare professionals. The findings may have practical implications for healthcare administrators and their staff.
Keywords: 8. Economic growth; 3. Good health